Jiwa Enterprenur dan Etika Bisnis Islam Santri Gontor Dalam Mengembangkan Air Mineral Amidas - Iriani, Dewi; Mufidah, Lailatul; Rosyid Ridho, Muhammad (Institut Agama Islam Negeri Ponorogo, 2021)
This article aims to determine the Darussalam Gontor Modern Islamic Boarding School's efforts in shaping the entrepreneurial spirit of the santri? Second, how is the development of Amidas Gontor Mineral Water in the perspective of Islamic Business Ethics? This article using field research (field research), the method used in this study using a qualitative approach, namely the author obtains data directly from sources from teachers/managers and students of the Darrusalam Gontor Islamic boarding school, Ponorogo. Research results 1) The Darussalam Gontor modern cottage's efforts in shaping the entrepreneurial spirit of the Santri, which are taught, have five characteristics, namely: confidence is cultivated to the students, by giving confidence in carrying out the production of Amidas Gontor brand mineral water—having continuous and innovative initiatives, in developing the business unit it holds and having achievement motives, which can provide the students with provisions to apply what they have learned after becoming alumni regarding entrepreneurship. The spirit of leadership, where the alumni who serve are entrusted to manage Amidas Gontor. Dare to take calculated risks, introduce the entrepreneurial results of the santri, events and expos are often held in the cottage, apart from the students, caretakers, guardians of Santri, and the wider community. 2) Development of Gontor Amidas mineral water in the perspective of Islamic business ethics principles; Unity/State; Obedience to worship is a belief in the existence of one God. Balance (Justice); evenly distributed. Free Will, done verbally for the Ponorogo area, the outer island area is done through an online application. The Pondok Gontor party is responsible for compensating for damage to the Ponorogo area outside the island. 3) Virtue: Truth and Honesty. Honest and true in establishing partnerships with agents, shops, distributors, retailers of mineral water Amidas.